Correlaction of Protein Intake, Consumption of Fruit and Vegetables, Sodium Intake in Packaged Food with the Incidence of Anemia - Gita Restiana; Saskiyanto Manggabarani; Rani Rahmasari Tanuwijaya (Journal of Nutrition Science, 2022)
Anemia among adolescents is still an important health problem due to adolescent growth. Anemia in adolescent girls is caused by irregular eating patterns, abstinence from eating eggs/meat/fish, a dislike of consuming vegetables, and eating habits of fast food and junk food. Objective: This study aims to determine the relationship between protein, vegetable, and fruit intake, and sodium intake in packaged foods with the incidence of anemia in adolescent girls at MA Darussa'adah Jakarta. Methods: The design of this research is a cross-sectional study with a purposive sampling technique according to the inclusion and exclusion criteria, totaling 37 respondents. This research was conducted in February 2022. The research instrument is a food recall form 2x24 hours to determine protein intake and sodium intake in packaged foods, SQ-FFQ form to determine the consumption of vegetables and fruits by interviewing respondents. Results: The statistical results of the Pearson correlation test (p 0.825) and a positive pattern of r (0.38), vegetables and fruit (p 0.333) with a positive pattern of r (0.164), sodium intake (p 0.724) with a positive pattern of r (0.60). Conclusion: there is no relationship between protein, vegetable, and fruit intake, sodium intake in packaged foods, and anemia in adolescent girls.